Online, Face-to-Face, or Blended Learning? Faculty and Medical Students' Perceptions During the COVID-19 Pandemic: A Mixed-Method Study - Atwa, Hani; Shehata, Mohamed Hany; Al-Ansari, Ahmed; Kumar, Archana; Jaradat, Ahmed; Ahmed, Jamil; Deifalla, Abdelhalim (Frontiers in Medicine, 2022)
Background COVID-19 pandemic forced educational institutions to adopt online methods which were inevitable to keep continuity of education across all academia after suspension of traditional educational systems. The aim of this study was to explore the experience of faculty and students of online and face-to-face learning, and their preference of the mode of learning after the pandemic. Methods This is a mixed-method study. Quantitative data was collected through a survey from 194 medical students and 33 faculty members, while qualitative data was collected through two focus group discussions with 9 students and another two with 13 faculty members. Quantitative variables were presented as means and standard deviations. Paired samples t-test and Chi-square test were used. Thematic analysis of qualitative data was used to code, interpret, and make sense of data. Results Mean scores of responses of faculty members and students were higher for face-to-face and blended learning compared to online learning in all survey statements with statistically significant differences. More than half of the students (53.1%) preferred the face-to-face mode of learning, while most of the faculty members (60.6%) preferred the blended mode of learning. Qualitative analysis identified five themes, namely: “Transforming the way theoretical teaching sessions are given,” “Face-to-face teaching at campus cannot be replaced for some types of education,” “Interaction in online sessions is limited,” “Problems and challenges of online examinations,” and “Technical issues and challenges of online education.” It revealed suggestions that at least 30% of the curriculum could be taught online post-COVID-19. Some aspects of clinically oriented teaching including history taking and case discussions can also be delivered online in the future. Faculty members and students reported that dealing with online education was not difficult, although the transition was not smooth. Conclusion Medical students and faculty members were in favor of face-to-face and blended modes of learning. However, they perceived online mode of learning as an acceptable adaptation in theoretical teaching and in some clinically oriented teaching including history taking and clinical case discussions. Although face-to-face education in medicine is irreplaceable, the blended mode of learning remains an acceptable and practical solution for the post-COVID era.